On New Linear Operator Associated with Gaussian Hypergeometric Functions - Ahmed, Firas Ghanim; Darus, Maslina; Gaboury, Sebastien (Journal of Informatics and Mathematical Sciences, 2015)
In the present paper, we introduce new classes \(_n^*(α,β,k,ρ)\) and \(_n(α,β,k,ρ)\) of meromorphic functions dened by means of the linear operator \(L^* (α,β) f (z)\) for function in \(U^* ={z:0 < |z| < 1}\) and investigate a number of inclusion relationships of these classes. We also derive some interesting properties of these classes.